2021
DOI: 10.3390/app11115260
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Summarization of User-Generated Videos

Abstract: The exponential growth of user-generated content has increased the need for efficient video summarization schemes. However, most approaches underestimate the power of aural features, while they are designed to work mainly on commercial/professional videos. In this work, we present an approach that uses both aural and visual features in order to create video summaries from user-generated videos. Our approach produces dynamic video summaries, that is, comprising the most “important” parts of the original video, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The results were compared with [ 26 ]. The authors presented a different approach and identified the samples based on video and audio recognition, contrary to our method, which contains only video.…”
Section: Resultsmentioning
confidence: 99%
“…The results were compared with [ 26 ]. The authors presented a different approach and identified the samples based on video and audio recognition, contrary to our method, which contains only video.…”
Section: Resultsmentioning
confidence: 99%
“…Miao et al [13] proposed an extractive model to integrate multimodal new data and extract keywords as the short title, with a reinforcement training method. Some works utilised a collection of visual, audio, and text modalities sourced from web blogs and multimedia streams to generate summaries [14][15][16][17]. Some works have been dedicated to generating multimodal output instead of only text or…”
Section: Multimodal Extraction Summarisationmentioning
confidence: 99%
“…The quantity of user-generated instructional videos posted online has exponentially increased in recent years due to the growing popularity of video-sharing platforms. Due to the amount of videos available online, there is a growing need for the effective methods to find and retrieve relevant videos [ 3 , 4 ]. In order to meet these needs, numerous researchers have employed the concept of video summarization to generate brief summaries from the videos [ [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%